Relationship quality and exhibitors’ sustainable willingness to participate in exhibitions: A sociocultural perspective - Wang, Pengfei; Liang, Liuke; Pan, Yu; Wang, Yu; Li, Linna; Chen, Yanyan; Tian, Yihan (Frontiers in Psychology, 2022)
Exhibition is a new economic business form in China. From a stakeholder perspective, all important roles in the context of hospitality and tourism are talents. From a socio-cultural perspective, interpersonal relationship quality plays a vital role in business and industrial operations. This constructs a causal model of relationship quality between exhibitors and exhibition organizers, and examined its influence on exhibitors’ willingness to sustainably participate in exhibitions. Data collected from a total of 251 exhibitors from 4 nation-representative exhibitions in Beijing were analyzed. The results found that the four antecedent variables—guanxi (as distinctive from relationship quality), service quality, communication, and exhibition effectiveness—have significant impacts on the relationship quality between exhibitors and exhibition organizers, which in turn, affect exhibitors’ willingness to participate in subsequent exhibitions (i.e., exhibitor loyalty). These findings provide a theoretical basis and policy recommendations talent management in exhibition context.